The activity of NADPH-oxidase of neutrophilic leukocytes in patients with chronic generalized periodontitis in aggregate with iron - deficiency anemia - I. A. Slavinsky; L. A. Skorikova; O. V. Tsymbalov (Кубанский научный медицинский вестник, 2015)
In patients with chronic generalized periodontitis in aggregate with iron-deficiency anemia revealed dysfunction of neutrophilic leukocytes caused by decreased activity of iron-containing components of antibacterial systems, in particular of NADPH-oxidase. Dental treatment of these patients is ineffective without the use of iron preparations.